Crystallization of self-fluxes of the system K2O−P2O5−MeIII2O3−MeIIO (MeIII – Al, Bi; MeII – Mg, Ca, Sr, Co, Ni, Zn) - Strutynska, N. Yu.; Livitska, O. V.; Zatovsky, I. V.; Slobodyanik, N. S. (Reports of the National Academy of Sciences of Ukraine, 2015)
The crystallization of self-fluxes of the system K2O−P2O5−MeIII2O3−MeIIO (MeIII – Al, Bi; MeII – Mg, Ca, Sr, Co, Ni, Zn) (molar ratios K/P = 0,85−1,30, MeII/MeIII = 1,0, MeIII/P = 0,30, and the range of temperatures 1000–680 ºC) is investigated. The analysis of the influence of the nature of alkaline metals on the interaction in the self-flux MeI2O−P2O5−MeIII2O3−MeIIO (MeI – K, Cs; MeII – Mg, Ca, Sr, Co, Ni, Zn; MeIII – Al, Bi) is done. The obtained crystalline phases are determined, by using X-ray powder diffraction, IR spectroscopy, and optical microscopy.